Finite element modeling of bond behavior between heat-damaged concrete and carbon fiber-reinforced polymer sheets. Issue 2 (3rd April 2023) - Obaidat, Yasmeen Taleb; Barham, Wasim S.; Hayajneh, Shireen Z.
ABSTRACT: In this study, several finite element (FE) models were constructed and validated with data from experiments that focused on bond behavior between heat-damaged concrete and carbon fiber–reinforced polymer (CFRP). Different parameters as the compressive strength of concrete, CFRP width and length, number of CFRP layers (one, two and three layers) and heat exposure level were considered. A concrete block of 150 mm width, 150 mm height and 300 mm span length strengthened using different configurations of CFRP sheets was used to investigate the bond behavior by means of single shear test. The results show a good congruence with the investigated studies. The results of this study showed that beyond a temperature of 500°C, there was a considerable deterioration in bond properties between CFRP sheets and concrete. Also, a slight enhancement in ultimate bond load was noticed for some cases at temperature of 300°C, especially for concrete specimens having highest compressive strength at room temperature. Finally, numerical study was performed to develop modification factor to Diab and Farghal (2014) bond model to account for effects of damage of concrete due to high temperature exposure.